2015
DOI: 10.1002/elsc.201400239
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Streptomyces diastatochromogenes 1628 to increase the production of toyocamycin

Abstract: Toyocamycin (TM) shows antifungal activity and can be used to treat plant diseases. TM is produced by Streptomyces diastatochromogenes 1628, but the production rate is always very low. Recently, the gene toyG was cloned; however, nothing was known about the influence of toyG on TM production. In this study, the rational combined co‐expression of toyG with frr encoding a ribosome recycling factor and vgb encoding Vitreoscilla hemoglobin was performed. Introduction of these genes in double‐ or triple‐combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…To improve TM production further, we subsequently engineered the toy cluster to increase transcription of all toy genes. In our earlier study, the constitutive promoter permE ∗ , which is commonly used for gene expression in streptomycetes, was selected to increase the expression of favorable genes to improve TM production in S. diastatochromogenes 1628 ( Ma et al, 2014b ; Tao et al, 2016 ). Siegl et al (2013) developed a synthetic promoter library for actinomycetes based on the −10 and −35 consensus sequences of the constitutive and widely used ermEp1 promoter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve TM production further, we subsequently engineered the toy cluster to increase transcription of all toy genes. In our earlier study, the constitutive promoter permE ∗ , which is commonly used for gene expression in streptomycetes, was selected to increase the expression of favorable genes to improve TM production in S. diastatochromogenes 1628 ( Ma et al, 2014b ; Tao et al, 2016 ). Siegl et al (2013) developed a synthetic promoter library for actinomycetes based on the −10 and −35 consensus sequences of the constitutive and widely used ermEp1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…TM is produced by Streptomyces diastatochromogenes 1628, but the production level is always very low ( Ma et al, 2014a ). In this context, efforts to improve TM production have been made by the overexpression of structural genes ( Tao et al, 2016 ) or favorable genes ( Ma et al, 2014a ; Ma et al, 2014b ) and the pathway-specific regulatory gene toyA ( Xu et al, 2019 ) or ribosome engineering technology ( Ma et al, 2016 ). Expression of an extra copy of toyG and frr led to a 65.5% increase in TM production ( Tao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ToyA is controlling toyB-and toyE-expression by binding to both promoter regions [18]. It has also been shown that overexpression of toyF and toyG results in an improvement of TM production [14,16]. Thus, toyA, toyB, toyE, toyF and toyG are influencing TM production.…”
Section: Overexpression Of Rhp Sd Increases the Transcriptional Level...mentioning
confidence: 99%
“…Streptomyces diastatochromogenes 1628 was shown to produce TM [15], but its limited TM yield is still a bottleneck for further industrialization and commercialization. To improve the synthesis level of TM, several methods from genetic modification to ribosome engineering have been applied to improve production [16][17][18]. In addition, it has been reported that TM is synthesized using GTP as the precursor by a multi-step reaction [19] (Figure S1).…”
Section: Introductionmentioning
confidence: 99%